PEOPLES OF THE INDIES: ANTI-JAPANESE PROPAGANDA FILM BY THE DUTCH - Andriyanto; Adi Putra Surya Wardhana; Dennys Pradita (Universitas Pendidikan Ganesha, 2022)
This study aims to analyze the Dutch propaganda film Peoples of the Indies. The Dutch East Indies experienced a difficult period during the 1930s. The economic turbulence had an impact on political movements in the Dutch East Indies. Japanese propaganda was getting more and more alluring at that time. The Dutch saw Japan as a threat in the late 1930s. Therefore, the Dutch needed to ask the United States for public support to protect the Dutch East Indies. A propaganda film entitled Peoples of the Indies was made. This research will examine (1) the reasons why the Peoples of the Indies film needs to be made; (2) the multimodality of the Peoples of the Indies film; (3) the influence of the Peoples of the Indies film in the Dutch East Indies. This study uses the historical method with a multimodality approach. The results showed that the propaganda film, Peoples of the Indies, needed to counter Japanese propaganda. In multimodality, this film built on the discourse of democracy and multiculturalism in their colonies. The influence of the film on the colony was completely absent. The film's failure was because the Dutch ignored the importance of Indonesian public support to only target the United States and its allies. Meanwhile, the Indonesian public was already influenced by Japanese propaganda, even before the country succeeded in defeating ABDACOM and the Dutch East Indies Government. The Javanese also welcomed the arrival of Japan openly.